IgG4-Related Esophageal Disease Presenting as Esophagitis with Chronic Strictures - Correia, Catarina (2021)
IgG4-related disease is a recently recognized autoimmune systemic disorder that has been described in various organs. The disease is characterized histologically by a dense lymphoplasmacytic infiltrate with IgG4-positive cells, storiform fibrosis, obliterative phlebitis, and can be associated with space-occupying lesions. IgG4-related disease involving the upper gastrointestinal tract is rare. We report the case of a 30-year-old female patient with a long-standing history of severe dysphagia and odynophagia. Symptoms persisted despite anti-acid therapy, and control esophagogastroduodenoscopy revealed endoscopic images consistent with a nontransposable stenosis in the proximal esophagus. An underlying autoimmune process was suspected, and topical immunosuppressants were tried to control her disease. The patient maintained disabling dysphagia secondary to chronic esophageal strictures. A diagnosis of probable IgG4-related disease was made after esophageal biopsies. Treatment attempts with topical corticosteroids was not associated with a significant improvement of the symptoms of dysphagia and odynophagia, possibly because of the chronic nature of the disease associated with a high fibrotic component. This report describes a case of IgG4-related esophageal disease presenting as chronic esophagitis with strictures. We also briefly review the main histopathological features and treatment options in IgG4-related disease.